Case for diagnosis. Keloidal cord-like lesion on the leg, - Flaviano da Silva Oliveira; Nadya Picanço Lopes; Carolina Talhari; Antonio Schettini (Sociedade Brasileira de Dermatologia, 2020)
Abstract We report a 74-year-old male presented to an outpatient dermatology clinic in Manaus, Amazonas, with a one-year history of pruritic, keloidal lesions on his left lower extremity. Histopathology showed round structures in reticular dermis. Grocott methenamine silver stain revealed numerous round yeasts with thick double walls, occurring singly or in chains connected by tubular projections. The diagnosis was lobomycosis. Although the keloidal lesions presented by this patient are typical of lobomycosis, their linear distribution along the left lower limb is unusual.